The influence of leadership, organisational climate, and the mediating role of trust on South African soldiers' willingness to deploy : an exploratory study - Makhathini, Thulile Nokwethemba (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.